ruby-changes:24919
From: nobu <ko1@a...>
Date: Sat, 15 Sep 2012 18:26:33 +0900 (JST)
Subject: [ruby-changes:24919] nobu:r36971 (trunk): test_parse.rb: eval locations
nobu 2012-09-15 18:26:21 +0900 (Sat, 15 Sep 2012) New Revision: 36971 http://svn.ruby-lang.org/cgi-bin/viewvc.cgi?view=rev&revision=36971 Log: test_parse.rb: eval locations * test/ruby/test_parse.rb: set eval locations. Modified files: trunk/test/ruby/test_parse.rb Index: test/ruby/test_parse.rb =================================================================== --- test/ruby/test_parse.rb (revision 36970) +++ test/ruby/test_parse.rb (revision 36971) @@ -12,7 +12,7 @@ end def test_else_without_rescue - x = eval <<-END + x = eval <<-END, nil, __FILE__, __LINE__+1 begin else 42 @@ -23,7 +23,7 @@ def test_alias_backref assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 alias $foo $1 END end @@ -36,7 +36,7 @@ a = false b = c = d = true assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 a &&= t.foo 42 b &&= t.foo 42 c &&= t.foo nil @@ -51,7 +51,7 @@ a = [nil, nil, true, true] assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 a[0] ||= t.foo 42 a[1] &&= t.foo 42 a[2] ||= t.foo 42 @@ -67,7 +67,7 @@ o.foo = o.Foo = o::baz = nil o.bar = o.Bar = o::qux = 1 assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 o.foo ||= t.foo 42 o.bar &&= t.foo 42 o.Foo ||= t.foo 42 @@ -81,7 +81,7 @@ assert_equal([42, 42], [o::baz, o::qux]) assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 $1 ||= t.foo 42 END end @@ -90,7 +90,7 @@ a = b = nil assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 a = t.bar "foo" do "bar" end.gsub "ob", "OB" @@ -104,7 +104,7 @@ a = nil assert_nothing_raised do - t.instance_eval <<-END + t.instance_eval <<-END, __FILE__, __LINE__+1 a = bar "foo" do "bar" end END end @@ -112,7 +112,7 @@ a = nil assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 a = t::bar "foo" do "bar" end END end @@ -136,7 +136,7 @@ end assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 c::foo, c::bar = 1, 2 c.Foo, c.Bar = 1, 2 c::FOO, c::BAR = 1, 2 @@ -149,7 +149,7 @@ def test_dynamic_constant_assignment assert_raise(SyntaxError) do - Object.new.instance_eval <<-END + Object.new.instance_eval <<-END, __FILE__, __LINE__+1 def foo self::FOO, self::BAR = 1, 2 ::FOO, ::BAR = 1, 2 @@ -158,13 +158,13 @@ end assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 $1, $2 = 1, 2 END end assert_raise(SyntaxError) do - Object.new.instance_eval <<-END + Object.new.instance_eval <<-END, __FILE__, __LINE__+1 def foo ::FOO = 1 end @@ -173,7 +173,7 @@ c = Class.new assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 c::FOO &= 1 ::FOO &= 1 END @@ -181,7 +181,7 @@ c = Class.new assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 $1 &= 1 END end @@ -189,13 +189,13 @@ def test_class_module assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 class foo; end END end assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 def foo class Foo; end module Bar; end @@ -204,7 +204,7 @@ end assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 class Foo Bar; end END end @@ -217,7 +217,7 @@ a = nil assert_nothing_raised do - o.instance_eval <<-END + o.instance_eval <<-END, __FILE__, __LINE__+1 undef >, / END end @@ -231,7 +231,7 @@ o.foo = o.Foo = o::baz = nil o.bar = o.Bar = o::qux = 1 assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 o.foo ||= 42 o.bar &&= 42 o.Foo ||= 42 @@ -246,7 +246,7 @@ a = nil assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 a = -2.0 ** 2 END end @@ -259,7 +259,7 @@ a = nil assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 o.foo 1 do|; a| a = 42 end END end @@ -268,25 +268,25 @@ def test_bad_arg assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 def foo(FOO); end END end assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 def foo(@foo); end END end assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 def foo($foo); end END end assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 def foo(@@foo); end END end @@ -295,7 +295,7 @@ def o.foo(*r); yield(*r); end assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 o.foo 1 {|; @a| @a = 42 } END end @@ -304,7 +304,7 @@ def test_do_lambda a = b = nil assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 a = -> do b = 42 end @@ -320,7 +320,7 @@ a = b = nil assert_nothing_raised do - o.instance_eval <<-END + o.instance_eval <<-END, __FILE__, __LINE__+1 a = foo 1 do 42 end.to_s b = foo 1 do 42 end::to_s END @@ -332,7 +332,7 @@ def test_call_method a = b = nil assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 a = proc {|x| x + "bar" }.("foo") b = proc {|x| x + "bar" }::("foo") END @@ -366,7 +366,7 @@ o = Object.new assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 def o.foo(a=42,*r,z,&b); b.call(r.inject(a*1000+z*100, :+)); end END end @@ -377,7 +377,7 @@ assert_raise(ArgumentError) { o.foo() } assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 def o.foo(a=42,z,&b); b.call(a*1000+z*100); end END end @@ -386,7 +386,7 @@ assert_raise(ArgumentError) { o.foo() } assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 def o.foo(*r,z,&b); b.call(r.inject(z*100, :+)); end END end @@ -398,19 +398,19 @@ def test_duplicate_argument assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 1.times {|&b?| } END end assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 1.times {|a, a|} END end assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 def foo(a, a); end END end @@ -418,7 +418,7 @@ def test_define_singleton_error assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 def ("foo").foo; end END end @@ -428,17 +428,17 @@ t = Object.new assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 def t.`(x); "foo" + x + "bar"; end END end a = b = nil assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 a = t.` "zzz" 1.times {|;z| t.` ("zzz") } END - t.instance_eval <<-END + t.instance_eval <<-END, __FILE__, __LINE__+1 b = `zzz` END end @@ -509,7 +509,7 @@ def test_parse_string assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 / END end @@ -568,7 +568,7 @@ def test_magic_comment x = nil assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 # coding = utf-8 x = __ENCODING__ END @@ -576,7 +576,7 @@ assert_equal(Encoding.find("UTF-8"), x) assert_raise(ArgumentError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 # coding = foobarbazquxquux_dummy_enconding x = __ENCODING__ END @@ -595,7 +595,7 @@ def test_dot_in_next_line x = nil assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 x = 1 .to_s END @@ -611,7 +611,7 @@ def test_embedded_rd assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 =begin END end @@ -675,7 +675,7 @@ eval %q(__ENCODING__ = 1) end assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 def foo FOO = 1 end @@ -685,7 +685,7 @@ def test_block_dup assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 foo(&proc{}) {} END end @@ -693,7 +693,7 @@ def test_set_backref assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 $& = 1 END end @@ -706,7 +706,7 @@ end r = nil assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 o[&proc{|x| r = x }] = 1 END end @@ -738,7 +738,7 @@ o = Object.new assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 x = def o.foo; end END end @@ -748,13 +748,13 @@ def test_assign_in_conditional assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 (x, y = 1, 2) ? 1 : 2 END end assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 if @x = true 1 else @@ -766,33 +766,33 @@ def test_literal_in_conditional assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 "foo" ? 1 : 2 END end assert_nothing_raised do x = "bar" - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 /foo#{x}baz/ ? 1 : 2 END end assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 (true..false) ? 1 : 2 END end assert_nothing_raised do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 ("foo".."bar") ? 1 : 2 END end assert_nothing_raised do x = "bar" - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 :"foo#{"x"}baz" ? 1 : 2 END end @@ -800,7 +800,7 @@ def test_no_blockarg assert_raise(SyntaxError) do - eval <<-END + eval <<-END, nil, __FILE__, __LINE__+1 yield(&:+) END end -- ML: ruby-changes@q... Info: http://www.atdot.net/~ko1/quickml/